Discovery of crustal xenolith-bearing Miocene post-collisional igneous rocks within the Yarlung Zangbo Suture Zone southern Tibet: Geodynamic implications - Hébert, Réjean; Guillaume, Lesage; Rachel, Bezard; Guilmette, Carl; Bédard, Émilie; Wang, Chengshan; Ullrich, Thomas David; Dostal, Jaroslav (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1265 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.63